1970
DOI: 10.1111/j.1469-8986.1970.tb01753.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Physiological and Psychological Measurements on Anxious Patients and Normal Controls

Abstract: Clinical, psychophysiological, and psychometric measurements were made on 20 normal controls and 30 anxious patients during rest and experimental stress. Resting forearm blood flow, a relatively new physiological index of anxiety, was found to correlate significantly with clinical and subjective ratings of anxiety, and with heart rate, number of spontaneous fluctuations of skin resistance, and amplitude of forearm EMG. It did not correlate significantly with any of the measures of depression. Resting forearm b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
2

Year Published

1974
1974
2002
2002

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 17 publications
2
20
2
Order By: Relevance
“…Because these results correspond with those from previous studies, the use of biofeedback training techniques as a mediator to the experience of state anxiety in helping profession trainees was not established. However, this study and those by Fontaine (197 5), Gibson (1977), and Meyer (Diblin, 1970;Kelly, Brown, and Shaffer, 1970;Thompson, 1976), the results of this research corresponds to the growing body of literature which indicates that correla tions between anxiety assessment measures are generally small and nonsignificant at worst, and unclear and confusing at best (Bowman, Roberts, and Giesen, 1978;Johnson and Spielberger, 1968). It is difficult to speculate on the reasons for such findings, however, this conclusion appears to be consistent with the operational definition of anxiety previously presented.…”
contrasting
confidence: 42%
See 3 more Smart Citations
“…Because these results correspond with those from previous studies, the use of biofeedback training techniques as a mediator to the experience of state anxiety in helping profession trainees was not established. However, this study and those by Fontaine (197 5), Gibson (1977), and Meyer (Diblin, 1970;Kelly, Brown, and Shaffer, 1970;Thompson, 1976), the results of this research corresponds to the growing body of literature which indicates that correla tions between anxiety assessment measures are generally small and nonsignificant at worst, and unclear and confusing at best (Bowman, Roberts, and Giesen, 1978;Johnson and Spielberger, 1968). It is difficult to speculate on the reasons for such findings, however, this conclusion appears to be consistent with the operational definition of anxiety previously presented.…”
contrasting
confidence: 42%
“…However, with both finger temperature and self-report measures there was a significant increase in state anxiety levels in helping profession trainees. (Fry, 1973 ;Pennscott and Brown, 1972;Rihani, 1973) person's reactions to it (Bowman, Roberts, and Giesen, 1978;Spielberger, 1972 (Kelly, Brown, and Shaffer, 1970;Leboeuf, 1974 This is in apparent conflict with other reported research findings Bowman, Roberts, and Giesen, 1978) in which both physiological and self-report measures detected significant increases in state anxiety during an inter view. The limitation of the research cited above is apparent when one realizes that the self-report measures were question naires developed by the investigators for use in their research.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Kelly and co-workers [Kelly, 1967;Kelly and Walter, 1968;Kelly et al, 1970] found increased forearm blood flow (FBF) levels among anxious patients. This led Williams et al [1973] to examine FBF under interview conditions.…”
mentioning
confidence: 99%